Costa Rica - Country Note on Climate Change Aspects in Agriculture - World Bank (Washington, DC, 2012)
This country note briefly summarizes information relevant to both climate change and agriculture in Costa Rica, with focus on policy developments (including action plans and programs) and institutional make-up. Like most countries in Latin America, Costa Rica has submitted one national communication to the United Nations Framework Convention on Climate Change (UNFCCC) with a second one under preparation. Land use change and forestry are the largest contributors to GHG emissions in the country. The emission reduction potential of the sector is large and several reforestation programs have been initiated. It is estimated that Central America produces less than 0.5 percent of global carbon emissions, but it is one the most vulnerable regions to climate change related impacts on the planet. Agriculture is highly vulnerable to climate variability, this coupled with problems of land degradation in the country. A greater emphasis on reducing soil degradation and developing and applying adequate insurance mechanisms can be placed for better management of public resources in light of natural disasters in the agriculture sector.